The Effect of Work-Life Balance, Work Environment, and Career Counseling on Employee Job Satisfaction at the KPP Pratama Surabaya Tegalsari - Ciputra, Hendra Dwi Haryadi; Purwanto, Purwanto; Rahayu, Sri (Neo Journal of economy and social humanities, 2026)
This study examined the effects of work–life balance, work environment, and career counseling on employee job satisfaction at KPP Pratama Surabaya Tegalsari. The research employed a quantitative causal associative design to analyze both partial and simultaneous relationships among variables. The population consisted of all 73 employees at KPP Pratama Surabaya Tegalsari, and a census method was applied so that the entire population served as research respondents. Data were collected using a structured questionnaire measured on a five-point Likert scale, with instruments adapted from established prior studies. Data analysis was conducted using SPSS version 20, including validity and reliability testing, classical assumption tests, multiple linear regression analysis, coefficient of determination, and hypothesis testing through t-tests and F-tests. The results indicated that work–life balance, work environment, and career counseling each had a positive and significant effect on employee job satisfaction. Among the three variables, work–life balance emerged as the most dominant factor influencing job satisfaction. Simultaneously, the three independent variables significantly explained employee job satisfaction, with a high explanatory power of the regression model. These findings highlight the importance of organizational support through balanced work arrangements, conducive work environments, and structured career counseling in enhancing job satisfaction within public sector institutions.